(untitled) (African Disability Rights Yearbook, 2021)
Lesotho is party to a number of international human rights instruments including those which provide for equality and non discrimination of women as well as those that guarantee the rights of persons with disabilities. This article discusses how Lesotho may fulfil its international human rights obligations to realise sexual and reproductive rights of women with disabilities. It explores the international legal framework on sexual and reproductive rights; in particular the standards and obligations contained in the UN Convention on the Rights of Persons with Disabilities (CRPD). It assesses the extent to which the legal and policy frameworks in Lesotho adhere to international standards and argues that alignment of the national legal framework with international standards is the starting point towards fulfilment of the state’s obligation to ensure that women with disabilities enjoy sexual and reproductive rights.